Determination of radioactive pollution from an open landfill - Baykara, O; Hasar, H; Öbek, E; Dogru, M (Springer, 2005)
This paper presents a case study of radioactive pollution of groundwater caused by leachate from an open landfill. Alpha- and beta-radioactivity analysis of the leachate from different points in the region and associated fountain water from a village down stream were carried out during four seasons. The alpha- and beta-radioactivity concentrations were under the detection limit in all samples and ranged between 0.07 and 2.17 Bq/l, respectively. The beta-radioactivity concentration from I-129, Cs-137 and Sr-90 individual radioisotopes were determined and their annual effective dose was calculated.
Keywords: I-129; Contamination; Surface; Waters; Rivers